Efficacy of parent management training in reduction of children's feeding problems - Shirin Zeinali; Vahideh Emanzadeh; Mohamd Ali Mazaher; Karine Tahmasian; Mansure Sadat Sadeghi (Gonabad University of Medical Sciences, 2017)
Feeding problems are common in infant and young children. These problems affect mother and child relationship. The current study sought to investigate the efficacy of parent management training in reducing children's feeding problems. The present study was a semi-experimental research based on pretest, posttest and follow-up design with a control group. 34 mothers whose children had feeding problems were chosen and randomly divided into control and experimental groups. Then, experimental group was intervened using training program for mothers for six sessions. Control group didn't receive any intervention. Mothers in the experimental and control groups were assessed in three time intervals (pretest, posttest and follow-up) by the questionnaire of feeding problems. Findings of repeated measure analysis indicated that training programs for parents significantly reduced the feeding problems. This finding confirmed that parent training program is an effective intervention for reducing feeding problems.